Song Policy on Radio MQ FM Yogya - Rhafidilla Vebrynda; Venn Okta Suryadarma (CHANNEL: Jurnal Komunikasi, 2022)
Each media has a characteristic correlated to its image. How a media is displayed has its own rules. Radio MQ FM is a network radio with Islamic nuances in Bandung. This radio is under the auspices of MQ FM Bandung and Yogyakarta Amikom University and has a segment of Indonesian Muslim families. In the midst of the proliferation of popular songs in Indonesia and even abroad, MQ FM has regulations, one of which is the selection of songs that are played on the radio. This is in line with the theory of gatekeeping in mass communication which explains the limitations in media routines that cannot present many things but make choices in presenting content. The gatekeeping process is carried out by the keeper, and in this case, a Music Director (MD). To discuss how the selection of songs in MQ FM Yogya, this study used a descriptive qualitative method. The data collection was in the form of observation, interviews and documentation. This study found that in determining songs at MQ FM, Yogya, MD paid attention to the type of music, lyrics, singers, audio quality and also the song duration